Studying diabetes through the eyes of a fish: microdissection, visualization, and analysis of the adult tg(fli:EGFP) zebrafish retinal vasculature - Wiggenhauser, Lucas; Murillo, Katharina; Dietrich, Nadine; Hammes, Hans-Peter; Kroll, Jens (JoVE. Video journal, 2017)
Here, we discuss a method protocol which will allow an easy analysis of the adult tg(fli:EGFP) zebrafish retinal vasculature as a fast...
Enthält auch Textversion
Gesehen am 10.10.2018
Wissenschaftlicher Film. Deutschland. 2017
Keywords: Film